The efficacy of modified Viennese manual perineal protection (VMPP) at second stage of labour - Nusee, Zalina; Jenal, Ruztini; Ismail, Hamizah (2018)
Introduction Modified VMPP method had been conducted by using a novel biomechanical model of perineum at New Technologies for Information Society, Pilsen, Czech Republic (NTIS). It evaluates the precise placement of the thumbs and index finger during tension of perineal tissue. The most effective modified VMPP method is initial position of fingers 12cm apart (x = + 6cm) on the x-axis, 2cm anteriorly from the posterior fourchette (y = + 2cm) on the y-axis. At the time of pushing till expulsion, the thumb and index finger were then moved 1cm toward midline on the x-axis. There was no movement on the y-axis. It was compared with hands-off delivery techniques. Stress distribution between modified VMPP method showed a wide variation in peak perineal tension from 72% to 102% compared with 100% for the hands-off technique.